Conversions from Normal to Abnormal Current‐Dependent ISC and from Abnormal to Normal Current‐Dependent RISC Processes in Exciplex‐Based OLEDs. Issue 16 (20th April 2022) - Zhao, Xi; Chen, Jing; Tang, Xiantong; Wu, Fengjiao; Ning, Yaru; Chen, Xiaoli; Xiong, Zuhong
Abstract: Intersystem crossing (ISC) and reverse ISC (RISC) are important spin‐mixing processes for obtaining high quantum efficiency in exciplex‐based organic light‐emitting diodes (EB‐OLEDs) and often show normal current ( I ) dependencies which weaken with increasing I . Surprisingly, herein, using magneto‐conductance (MC) as a fingerprint probing tool, an unreported conversion from normal to abnormal I ‐dependent ISC processes is observed at 300 K from relatively‐unbalanced EB‐OLEDs with the low electron‐injection barrier and the high hole mobility. More amazingly, after improving carrier injection balance through replacing the hole‐injection layer, a conversion from abnormal to normal I ‐dependent RISC processes with increasing I is observed from the relatively‐balanced EB‐OLEDs for the first time. These two conversions are reasonably analyzed by fitting and decomposing MC traces of the devices. Furthermore, transition I of the conversion from abnormal to normal I ‐dependent RISC processes decreases from 50 to 5 μA as the temperature reduces from 300 to 150 K, and only the normal I ‐dependent RISC process is observed at 100 and 20 K due to high driving voltages. Obviously, this work deepens the full understandings of I ‐dependent ISC and RISC processes in EB‐OLEDs and has the potential applications for the achievement of high‐performance devices. Abstract : Conversions from normal to abnormal current‐dependent intersystem crossing (ISC) and from abnormal to normal current‐dependent reverse ISC processes are observed from two interfacial exciplex‐based organic light‐emitting diodes with different hole‐injection layers. These two conversions are analyzed by fitting and decomposing magneto‐conductance traces of the devices. This work deepens the understandings of physical microscopic processes for exciplex states formed at the interface.